What goes up must come down: dynamics of type 1 interferon signaling across the lifespan - Hartnell, Lucy; Agudelo-Romero, Patricia; Montgomery, Samuel T.; Ben-Othman, Rym; Verhasselt, Valerie; Stick, Stephen M.; Kollmann, Tobias R. (Frontiers in Immunology, 2025)
Type 1 interferons (T1IFNs) are typically expressed in low concentrations under homeostatic conditions, but upon pathogenic insult or perturbation of the pathway, these critical immune signaling molecules can become either protectors from or drivers of pathology. While essential for initiating antiviral defense and modulating inflammation, dysregulation of T1IFN signaling can contribute to immunopathology, making it and its associated pathways prime targets for immune evasion and disruption by pathogens. This review focuses on the changes in T1IFN signaling across the lifespan, with particular emphasis on the role of the Stimulator of Interferon Genes (STING) pathway in autoimmune and infectious disease susceptibility, especially in the context of viral infections. Aging is associated with diminished T1IFN responsiveness, partially resulting from chronic stimulation of the STING pathway, which contributes to increased susceptibility and impaired viral clearance. Conversely, neonates and young children also show increased vulnerability to certain viral infections, but whether this is driven by T1IFN differences or another mechanism remains incompletely understood. Despite growing interest in T1IFN-based immunotherapies, pediatric and elderly populations remain underrepresented in clinical trials. Here, we advocate for a deeper molecular and systems understanding of how the interferon response evolves across the human lifespan, to inform age-tailored therapeutic approaches and more inclusive study designs, thereby improving outcomes in both the youngest and oldest patients.